A bad day for voodoo - Strand, Jeff. (Naperville, Ill. : Sourcebooks Fire, 2012)
When your best friend is just a tiny bit psychotic, you should never actually believe him when he says, "Trust me. This is gonna be awesome." Of course, you probably wouldn't believe a voodoo doll could work either. Or that it could cause someone's leg to blow clean off with one quick prick. But I've seen it. It can happen. And when there's suddenly a doll of YOU floating around out there - a doll that could be snatched by a Rottweiler and torn to shreds, or a gang of thugs ready to torch it, or any random family of cannibals - really, do you need the danger here spelled out for you? - well, you know that's just gonna be a really bad day...
Keywords: Vodou -- Juvenile fiction; Humorous stories; Horror stories